Examining Stakeholders' Perceptions of Mining Impacts and Corporate Social Responsibility. (21st July 2014) - Viveros, Hector
Abstract: This paper aims to provide a better understanding of multistakeholder perceptions of corporate social responsibility (CSR) in connection with mining industry impacts. While there is significant research about CSR, there is a lack of understanding in the area of specific stakeholders' perceptions within the extractive industry, particularly in a developing country like Chile. The findings reveal that stakeholders perceive mining impacts on social and environmental domains negatively in contrast to a positive perception about economic impacts. CSR is addressed in terms of social and environmental responsibilities, but is also perceived negatively as mere rhetoric, or simply as a marketing campaign. These perceptions reflect an anti‐trade‐off sentiment, revealing that CSR cannot be used as a tool to compensate negative mining impacts. Copyright © 2014 John Wiley & Sons, Ltd and ERP Environment